1978
DOI: 10.1126/science.199.4331.879
|View full text |Cite
|
Sign up to set email alerts
|

Residential Natural Gas Consumption: Evidence That Conservation Efforts to Date Have Failed

Abstract: A new short-term natural gas consumption model is developed, tested against American Gas Association sales data, and applied to the question of the effectiveness of conservation efforts. The results indicate that unit residential gas-heating sales per heating degree-day have remained constant in four major gas-consuming regions during the period 1974 to 1976 and that heating sales have not been affected by the recent sharp changes in price.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1980
1980
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Empirically determined relationships between heating degree-days and fuel consumption (Lehman and Warren, 1978;Quayle and Diaz, 1980) can then be applied to the population-weighted heating degree-day values to estimate current or future requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Empirically determined relationships between heating degree-days and fuel consumption (Lehman and Warren, 1978;Quayle and Diaz, 1980) can then be applied to the population-weighted heating degree-day values to estimate current or future requirements.…”
Section: Discussionmentioning
confidence: 99%
“…The engineering basis for this approach is developed by Harris et al (1965) and its empirical power is demonstrated shortly after the first oil price shock (e.g. Mitchell et al (1974); Lehman and Warren, 1978;Quayle and Diaz, 1980;Lecomte and Warren, 1981). Based on this success, using statistical techniques to quantify the relation between heating and/or cooling degree days and energy consumption is the standard methodology used by those seeking to assess the effect of climate change on energy consumption (e.g.…”
Section: Introductionmentioning
confidence: 99%